Clinical significance of type 2 iodothyronine deiodinase polymorphism. Issue 5 (3rd September 2018) - Maino, Fabio; Cantara, Silvia; Forleo, Raffaella; Pilli, Tania; Castagna, Maria Grazia
ABSTRACT: Introduction: Biological activity of thyroid hormones (TH) is regulated by enzymes known as deiodinases. The most important is represented by the type 2 deiodinase (D2), which is the main T4-activating enzyme, ubiquitous in human tissues and therefore essential in many metabolic processes. A single nucleotide polymorphism (SPN) of D2, known as Thr92Ala (rs225014), has been reported in the general population while other polymorphisms are less frequently described. Areas covered: Several authors investigated the potential metabolic effect of these polymorphisms in the general population and in specific groups of patients. Thr92Ala polymorphism was mainly studied in patients with autoimmune or surgical hypothyroidism and in patients with physical/psychological disorders that could be related to an overt hypothyroidism. Susceptibility to develop more severe type 2 diabetes or insulin resistance has also been evaluated. Commentary: There is an increasing evidence that the presence of D2 polymorphisms may play a pivotal role in a better definition and customized therapeutic approach of patients with hypothyroidism and/or type 2 diabetes, suggesting that these patients should be screened for D2 polymorphisms. Nevertheless, further research should be performed in order to clarify the association between D2 polymorphisms, metabolic alterations and clinical conditions of the carrier patients.